Morbilidad y mortalidad en pacientes mayores de 60 años con fractura de cadera en el Hospital Universitario San Vicente Fundación, de Medellín, Colombia (2012)
ABSTRACT: Clinical, radiological, and functional outcomes as well as postoperative complications among adults aged 60 years or more with hip fractures have been extensively described in the medical literature; nonetheless, information is rather limited concerning this lesion in Antioquia, Colombia. Between March 2009 and June 2010, 106 elderly patients (mean age 79 years, 83 of them women) were surgically treated for hip fracture at a third-level hospital in Medellín, Colombia. Ninety two patients (86.6%) had two or more chronic diseases associated with the hip fracture. Early postoperative complications occurred in 40 patients (37.7%), most of them unrelated to the surgical intervention. Out of the 79 patients followed at six months, only 25 (31.6%) had recovered a gait pattern similar to the previous one. These results were similar to those published by other authors; they show that much of the morbidity and mortality of these patients is associated with their underlying medical conditions. The importance of this work lies in determining the characteristics of our elderly population with hip fractures as a basis to design management protocols in Colombian institutions that allow an improvement in the functional results of these patients.